1997
DOI: 10.1080/004982597240343
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the calcium antagonist, mibefradil (POSICORTM, Ro 40-5967). Part III. Comparative pharmacokinetics of mibefradil and its major metabolites in rat, marmoset, cynomolgus monkey and man

Abstract: 1. The metabolism of mibefradil has been examined in rat, marmoset, cynomolgus monkey and man after single and multiple oral administration. 2. Metabolites typically represent between 50 and 80% of the circulating drug-related material after single oral doses of mibefradil to man, rat and marmoset. They arise by a combination of enzymatic processes: cytochrome P450-mediated oxidation at saturated and unsaturated carbon atoms, cytochrome P450-catalysed dealkylation and hydrolysis of the ester side-chain. 3. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…The IC 50 and K i of NNC55-0396 are 19-fold higher than that of mibefradil. The higher IC 50 and K i values observed for CYP3A4 in human liver microsomes compared with the values for recombinant CYP3A4 may result from the presence of other microsomal proteins that bind to the inhibitors, or to the presence of other enzymes that can metabolize the inhibitors, thus making them less available to inhibit the targeted enzyme (Wiltshire et al, 1997a). Moreover, the difference could have been contributed by different substrates being used.…”
Section: Downloaded Frommentioning
confidence: 94%
See 3 more Smart Citations
“…The IC 50 and K i of NNC55-0396 are 19-fold higher than that of mibefradil. The higher IC 50 and K i values observed for CYP3A4 in human liver microsomes compared with the values for recombinant CYP3A4 may result from the presence of other microsomal proteins that bind to the inhibitors, or to the presence of other enzymes that can metabolize the inhibitors, thus making them less available to inhibit the targeted enzyme (Wiltshire et al, 1997a). Moreover, the difference could have been contributed by different substrates being used.…”
Section: Downloaded Frommentioning
confidence: 94%
“…It has been shown that these P450s participate in the metabolism of approximately 80% of therapeutic drugs (Wienkers and Heath, 2005). To obtain a preliminary look at the P450 inhibitory profiles for mibefradil and NNC55-0396, two concentrations of the inhibitors were chosen, 100 nM and 10 M. These two concentrations represent the low and the high concentrations and cover the range of therapeutic plasma concentrations of the inhibitors because it has been reported that the human therapeutic plasma concentration of mibefradil ranges from 300 to 1000 ng/ml after doses of 50 to 100 mg/day, which correspond to 0.5 to 1.8 M mibefradil (Wiltshire et al, 1997a;Welker and Banken, 1998). At 100 nM, mibefradil exhibited more than a 2-fold greater inhibition than NNC55-0396 for CYP3A4 (63 and 27%, respectively, p Ͻ 0.001) (Fig.…”
Section: Comparison Of Nnc55-0396's P450 Inhibition Profile Withmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, cell toxicity was apparent when hiPS-CMs were treated with the drugs for > 24 hr at the concentrations described below (data not shown). For (Bachmann et al, 1997), mibefradil (Wiltshire et al, 1997), and terodiline (Hartigan-Go et al, 1996). The concentration column shows treatment concentrations of the drugs.…”
Section: Resultsmentioning
confidence: 99%